Ceramic membrane cross-flow microfiltration for beer recovery from tank bottoms - Bugan, S. G.; Dömény, Z.; Šmogrovičová, D.; Švitel, J.; Schlosser, Š.; Stopka, J. (BrewingScience, 2000)
Cross-flow microfiltration with ceramic membranes was applied for beer recovery from tank bottoms. The cross-flow microfiltration was optimised using model yeast suspension and the effects of pore size, flow speed and transmembrane pressure were characterised. Using 200 μm pore-size membranes and back-flush in 5 min intervals during filtration of tank bottoms, filtration rate 20 kg/m2 h-1 compared to 3 kg/m2 h-1 without back-flush was achieved. The quality of beer recovered from tank bottoms was extensively evaluated. Increased values of some beer components were found in recovered beer when 200 μm membranes were used: bitterness increased from 20 to 36 °EBC, total nitrogen from 78.4 to 172.1 mg/100 ml, polyphenols from 20.4 to 56.4 mg/l and diacetyl from 0.11 to 0.41 mg/l. Pore-size in range 100-500 μm has effect on filtration rate but no influence on beer quality. Some parameters of recovered beer, such as extract, alcohol, pH are not changed. Analyse of 7 fractions collected during beer recovery showed that values are generally increased in last fractions.